2022
DOI: 10.3390/su142114413
|View full text |Cite
|
Sign up to set email alerts
|

Sustaining Workforce Engagement: From Mindfulness to Psychological Flourishing

Abstract: (1) Background: Practising mindfulness has been suggested in several recent media reports to help employees reduce stress in their effort to balance work and life pressures, especially during the pandemic when they have to work from home. During COVID-19, organisations have also struggled to effectively engage, retain and sustain employees when managing their work remotely. It is uncertain whether there is a close link between mindfulness and sustained workforce engagement. Although data were collected prior t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1
1

Relationship

1
4

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 52 publications
0
1
0
Order By: Relevance
“…For instance, a review of empirical studies concluded that mindfulness increased behavior regulation, reduced psychological symptoms, and enhanced psychological well-being (Keng et al, 2011). Likewise, Brown and Ryan (2003) and Zheng and Gunasekara (2022) also found a positive association between mindfulness and psychological well-being. Research also supports a positive link among self-compassion, resilience, optimism, and mindfulness among nurses and nursing leaders (Lin et al, 2020;Stagman-Tyrer, 2014).…”
Section: Conservation Of Resource Theorymentioning
confidence: 99%
“…For instance, a review of empirical studies concluded that mindfulness increased behavior regulation, reduced psychological symptoms, and enhanced psychological well-being (Keng et al, 2011). Likewise, Brown and Ryan (2003) and Zheng and Gunasekara (2022) also found a positive association between mindfulness and psychological well-being. Research also supports a positive link among self-compassion, resilience, optimism, and mindfulness among nurses and nursing leaders (Lin et al, 2020;Stagman-Tyrer, 2014).…”
Section: Conservation Of Resource Theorymentioning
confidence: 99%